DESIGNAND EVALUATION OF TETRA-PAK CONTAINERS' RECYCLING PLANT ON A SMALLSCALE - Inche Mitma, Jorge (2004)
This study deals about the design and evaluation of Tetra Pak containers' recycling plant on a small scale. The basic Plant Engineering was found from the information gathered. Some aspects included were: product design, process design, equipment design and costs evaluation, with the aim of determining its technical, economical and environmental capability for its implementation.